The effect of euglycemic hyperinsulinemia on cerebral cortical glucose metabolism in newborn beagles - Trindade, Cleide [UNESP]; Huang, Marian [UNESP]; Hulman, Sonia [UNESP]; Reef, Susan [UNESP]; Kliegman, Robert [UNESP] (Springer Nature, 1988)
There is a paucity of information on the significance of insulin on neonatal cerebral glucose metabolism. The effect of insulin on neonatal cerebral glucose uptake and cerebral cortical metabolic intermediates was investigated with the euglycemic hyperinsulinemic clamp in unanesthetized beagles during the first day of life. Insulin was infused at various rates to sustain an elevated steady state plasma insulin concentration in individual pups. Furthermore, blood glucose and 2-deoxyglucose levels were also maintained (clamped) in a steady state by infusion of glucose and 2-deoxy-[14C]-gIucose. Mean (± SD) plasma insulin levels were 20 ± 12 and 2971 ± 3386 (33-14330) nU/ml in control and hyperinsulinemic pups. Blood glucose concentration was 4.43 ± 2.64 mM during basal periods and 4.54 ± 2.87 mM during the clamp period in study pups. Basal fasting glucose utilization in study pups was 43.9 ± 24 μmol/kg/min and increased to 60.9 ± 35.2 ^mol/ kg/min (p < 0.001) during hyperinsulinemia. Immediately after the euglycemic hyperinsulinemic clamp or fasting in control pups, the cerebral cortex was frozen to the temperature of liquid nitrogen. No differences were noted for any cerebral cortical intermediate between the two pup groups. In addition, there was no relationship between the cerebral intermediates concentration when analyzed as a function of plasma insulin levels. The uptake of cerebral 2-deoxyglucose was analyzed as a function of plasma insulin concentration (120-6900 μU/ml). Brain tissue demonstrated a positive linear relationship for 2-deoxyglucose uptake as a function of plasma insulin concentration. Although static determination of brain metabolites were not influenced by hyperinsulinemia, there was a positive effect of insulin on cerebral glucose uptake. Either directly or indirectly, insulin may increase brain glucose utilization in the newborn dog. © 1988 International Pediatric Research Foundation, Inc.